Balancing value and burden: the Centers for Medicare & Medicaid Services electronic Clinical Quality Measure (eCQM) Strategy Project. (12th August 2021) - Schreiber, Michelle; Krauss, Deborah; Blake, Bridget; Boone, Edna; Almonte, Rose
Abstract: Healthcare is undergoing a digital transformation, and the Centers for Medicare & Medicaid Services (CMS) aims to help providers navigate the clinical quality improvement landscape. In December 2017, CMS launched the Electronic Clinical Quality Measure (eCQM) Strategy Project. This article consists of 2 parts. The first part describes stakeholder outreach aimed to identify burdens and recommendations related to eCQM implementation and reporting. The second part describes how these burdens were addressed by CMS and how to engage in the digital transformation journey. Six themes emerged from the stakeholder feedback: Alignment, Value, Development Process, Implementation and Reporting Processes; EHR certification process; and Communication, Education, and Outreach. CMS and its partners addressed over 100 recommendations to improve the eCQM development, implementation, and reporting experience by creating implementation strategies. This included the development of new tools, such as the Measure Collaboration (MC) Workspace and ongoing testing of Fast Healthcare Interoperability Resources (FHIR)-based standards for quality measurement. CMS is sharing this summary of the eCQM Strategy Project to reflect CMS' interest in stakeholder engagement and burden reduction, increase awareness of available resources, and encourage continued engagement throughout this digital transformation in quality reporting.